TINJAUAN HAMBATAN SAMPING, KAPASITAS DAN TUNDAAN LALU LINTAS PADA SIMPANG TIDAK BERSINYAL DIKOTA MATARAM - ROHANI ROHANI; HASYIM HASYIM (Universitas Mahasaraswati K. Mataram, 2023)
On several roads in the city of Mataram, such as the Dr. Wahidin road, there are many shops that do not have enough parking space, so many vehicles are parked on the shoulder of the road and even on the road. The presence of pedestrians crossing the road and the activity of vehicles entering/exiting the road affect the speed of traffic, and the capacity of the road so that at certain hours there are frequent traffic jams. This of course will have an impact on the delay at the intersection of Dr. Wahidin. As for the Caturwarga street, there are schools, hospitals and shops that do not have sufficient parking space, many vehicles that drop off and pick up passengers and vehicles that enter and leave the land use side of the road. Of course, this condition affects the smooth flow of traffic, so it has an impact on delays at the Catur Warga intersection. This study analyzes side resistance, capacity and delay at unsignalized intersections on Caturwarga and Dr. Wahidin roads. The total of this side resistance will be used to analyze how much influence it has on the delay using the 1997 MKJI method. The results of the analysis at the Catur Warga intersection have side friction, and the delays are 790.7 events/hour, 16.63 seconds/smp. Meanwhile, at the Dr. Wahidin intersection, the side friction and delays are 403.1 events/hour and 17.00 seconds/pcu, respectively. From the results of regression analysis, side barriers affect traffic delays by 89.7% and at Dr. Wahidin intersections by 79.7%. Partially at the Catur Warga intersection, the side friction variable that has the most influence on delays is Exit/Entrance Vehicles on the land use side of the road (EEV). On the Dr. Wahidin road, the side obstacle variable that has the most influence on delays is Pedestrians (PED).